The Effect of Dental and Oral Health Education Using Methods Demonstration of Students' Level of Toothbrushing Knowledge Mental retardation SLB Jenetallasa Gowa Regency - Manggarsari, Yayi; Zulkarnaian, Zulkarnaian; AR, Aisyah; Jusmar, Sri Wahyuni (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Mentally retarded children are children who experience mental retardation which is indicated by intelligence functions below average, experiencing limitations in function intelligence and adaptive behavioral functions such as self-care communication, social skills, security, and academics are one of the obstacles to obtaining knowledge that is still lacking, especially in the field of dental and oral health. This research aims to determine the effect of oral health education using the demonstration method on the level of knowledge of toothbrushing in mentally retarded SLB students Jenetallasa, Gowa district. The benefit of this research is to provide information on mentally retarded children regarding the importance of maintaining healthy teeth and mouth. This type of research using Quasy Experimental Design with a One group Pret-test and approach Post-test. Research location at SLB Jenetallasa, Gowa Regency on 11-13 October 2023. Analysis of Wilcoxon signed Rank statistical test data. The results obtained are ÿ value= 0.000. This shows that there is an increase in toothbrushing knowledge among students with intellectual disabilities. The conclusion of this research is that there is an influence of oral health education using the demonstration method on students' level of toothbrushing knowledge mentally retarded SLB Jenetallasa Gowa district. It is recommended for mentally retarded students always apply how important it is to maintain healthy teeth and mouth and how to brush your teeth properly and correctly.